The Effect Of Selling Expenses On Business Profit Of California Papaya Farm Owned By Mr. Iswan Hadi Winarto In Penanjung Panjang Atas Kabupaten Kepahiang Regency - Sumantri, David Ajun; Afriani, Sulisti; Febliansa, Muhammad Rahman (Utami Publisher, 2025)
This study aims to determine the effect of selling expenses on business profit in the California papaya enterprise owned by Mr. Iswan Hadi Winarto in Penanjung Panjang Atas Kabupaten Kepahiang Regency. The research uses a quantitative approach with a simple linear regression analysis method. Data were obtained from primary sources through direct observation and secondary data from sales notes and financial records covering the period 2022–2024. The variables used consist of selling expenses (X) and business profit (Y), with selling expenses including capital expenditure, packaging, harvesting wages, and distribution costs. The analysis was conducted using SPSS software to test normality, regression, coefficient of determination (R²), and partial significance (t-test). The results showed that selling expenses have a positive and significant effect on business profit with the simple linear regression, the result is Y = -65.519 + 1.268X + 125. The simple linear regression test indicated a significance value of 0.000 < 0.05 and a correlation coefficient (R) of 0.868, showing a very strong relationship between the two variables. The determination coefficient (R²) value of 0.746 means that 74.6% of business profit variation can be explained by selling expenses, while the remaining 25.4% is influenced by other factors not included in the model. This finding implies that efficient management of selling expenses—particularly in distribution and packaging—can substantially increase business profitability.